Interactive Video Tutorial Media: Volleyball Smash Skill Learning Outcomes at Senior High School - Indra Wisman; Syahruddin Syahruddin; Wahyuni Wahyuni (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The lack of effective and structured learning media often hinders the development of complex motor skills, particularly volleyball smashing abilities, among high school students. This study aimed to determine the effect of interactive video tutorial media on volleyball smash learning outcomes at Senior High School 1, Takalar. This study employed a quasi-experimental method with a pre-test and post-test control group design. The sample consisted of 40 students divided into an experimental group (n=20) using interactive video tutorials and a control group (n=20) using conventional methods. The research instrument used was a validated volleyball smash skills test. Data analysis included normality tests, homogeneity tests, and t-tests with a significant level of 0.05. The results indicated that the control group showed no significant difference between pre-test and post-test scores, with the average score remaining stable at 10.00 (p=0.231 > 0.05). In contrast, the experimental group experienced a highly significant increase in the average score from 16.05 to 27.05 (p=0.001 < 0.05). These findings provide strong empirical evidence that interactive video tutorials are significantly more effective in helping students visualize and adopt complex biomechanical movements compared to traditional methods. This research confirms that integrating interactive technology is a valid educational solution for optimizing physical education learning outcomes at the senior secondary level.